South Korea's Transformation into an Imperialist Power. Issue 2 (3rd April 2021) - Pröbsting, Michael
ABSTRACT: Due to a combination of specific factors South Korea experienced a rapid process of industrialization and capital accumulation. This process has resulted in the country's transformation from a semi-colony dominated by US imperialism in 1945 into an emerging imperialist state in the 2000s. Today South Korea's economy is dominated by large corporations—the chaebols—which have dominated the domestic market for a good few decades. These corporations, moreover, export not only commodities but also capital. As a result there has been a massive increase in foreign investment by Korean capitalists, both in imperialist countries and in countries of the South. Today, South Korea's chaebols have secured a prominent place among the top global corporations. The chaebols usually consist of a vast network of formally independent firms, but they are united under the common administrative and financial control of a single family via a complex cross-shareholding structure. South Korea's imperialism still faces some limitations, especially in the political field given the presence of US troops and Washington's ongoing influence in Seoul's ruling circles. However, the dramatic economic rise of South Korean capital has created the preconditions to shed these political limitations too in the foreseeable future.